2021
DOI: 10.1186/s12889-020-10082-z
|View full text |Cite
|
Sign up to set email alerts
|

Health care provided to recent asylum-seeking and non-asylum-seeking pediatric patients in 2016 and 2017 at a Swiss tertiary hospital - a retrospective study

Abstract: Background Asylum-seeking children represent an increasing and vulnerable group of patients whose health needs are largely unmet. Data on the health care provision to asylum-seeking children in European contexts is scarce. In this study we compare the health care provided to recent asylum-seeking and non-asylum-seeking children at a Swiss tertiary hospital. Methods We performed a cross-sectional retrospective study in a pediatric tertiary care hosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our findings did not suggest a single pattern regarding migrants' access to and use of EDs. Some studies [39,50,54] reported a higher frequency of ED visits among migrants, while others [44,57] reported a higher frequency among non-migrants. According to some studies, migrants visit the ED for more urgent conditions compared to the host populations [51], while other studies report lower triage codes among migrants than non-migrants [46,49,50].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings did not suggest a single pattern regarding migrants' access to and use of EDs. Some studies [39,50,54] reported a higher frequency of ED visits among migrants, while others [44,57] reported a higher frequency among non-migrants. According to some studies, migrants visit the ED for more urgent conditions compared to the host populations [51], while other studies report lower triage codes among migrants than non-migrants [46,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, migrants visit the ED for more urgent conditions compared to the host populations [51], while other studies report lower triage codes among migrants than non-migrants [46,49,50]. There is disagreement about whether migrants are at greater [39,44], or lesser [46,58,59] risk of hospitalization than non-migrants. As for discharge rates, migrants tend to leave the hospital against medical advice (AMA) more frequently than the host population [59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations